Impact of micro-economic variables on stock prices in Malaysia and Philippines / Sabariah Mohamed - Mohamed, Sabariah (2020)
The study examines the impact of macroeconomic variables on stock prices in Malaysia and Philippine. This study focuses on Kuala Lumpur Composite Index (KLCI) and Philippine Stock Exchange Index (PSE). Stock markets, where bonds and share are issued and traded through exchanges and over-the-counter markets. Stock markets, are important for the development of an economy. Thus, acknowledge and understand the variables that can influence the condition and performance of the stock market are important to individuals, businesses, and future investors. The macroeconomic variables that are being utilized in this analysis are money supply (MS), exchange rate (ER), gross domestic product (GDP) and the time horizon of this study is from 1995 to 2019 which is 25 years and the data collection is in a yearly basis. Multiple Linear Regression is used as methodology. The test used includes descriptive analysis, correlation analysis, regression analysis which comprises the T-test, F-test, and R-square. Those are econometric tests that are given to examine the correlation among macroeconomic variables and the stock prices. The outcome of this study is a significant relationship toward stock price in Malaysia and the Philippines. This study can help as a guide to future investors and researchers in acknowledging and understanding the significant relationship impacting on macroeconomic variables and stock prices.